Phenomenon and mechanism of ion diffusion at Co-fired joint interface of NiZn Ferrite/MCT ceramic heterostructure. Issue 12 (15th June 2023) - Zhang, Hanyu; Yu, Zhong; Jiang, Xiaona; Zhang, Xiaofeng; Su, Qianfa; Zhuo, Jie; Wu, Chuanjian; Li, Qifan; Sun, Ke; Lan, Zhongwen
Abstract: Nickel-zinc ferrite (NZF) discs and magnesium calcium titanite (MCT) dielectric ceramic discs were laminated and co-fired to prepare NZF/MCT bi-layer laminated heterostructure samples. The sintering shrinkage of NZF and MCT was matched well via adjusting the sintering temperature. Ion diffusion curves at the co-fired joint interface were derived by electron-probe microanalysis (EPMA) and fitted basing on infinite diffusion coupling model. Ion diffusion mechanism at the co-fired joint interface was investigated in detail. The results show that Zn 2+ ions have the highest diffusion coefficient because of the smaller ion radius which is benefit for interstitial diffusion, while Ca 2+ ions have the lowest diffusion coefficient and segregate along the interface of MCT side. Fe 3+ ions have the biggest diffusion width because of the interstitial diffusion in the incompletely densified MCT. Sintered at 1260 °C, the maximum interdiffusion width is narrow to be about 102 μm. With increasing temperature, ion diffusion coefficient and diffusion distance both go up obviously. Highlights: Nickel-zinc ferrite (NZF) discs and magnesium calcium titanate (MCT) dielectric ceramic discs were co-fired to prepare heterostructure samples. The microscopic morphology and EDS mappings near the interface of NZF/MCT were observed and identified, respectively. Cations concentration curves were derived by EPMA and fitted. The diffusion width and diffusion coefficient were determined. The ion diffusion mechanisms at co-fired joint interface were investigated in detail.